Genderfucking as a Critical legal Methodology - Ashley, Florence (McGill Law Journal / Revue de droit de McGill, 2024)
In this essay, I theorize genderfucking as a critical legal methodology. Genderfucking is defined by its focus on the needs and experiences of those who ‘fuck’ with gender, resisting attempts at gender governance through laws, policies, and practices. Adopting a politics of messiness, genderfucking is critical of recognition and calls into question the state’s legitimacy in defining and policing gender categories. Genderfucking offers a rich and fertile approach for analyzing a social, political, and legal world indelibly marked by regimes of gender and, in so doing, steps on the path towards gender liberation.